A novel malformation complex of bilateral and symmetric preaxial radial ray-thumb aplasia and lower limb defects with minimal facial dysmorphic features: a case report and literature review - Al Kaissi, Ali (BioMed Central, 2008)
INTRODUCTION: Radial hemimelia is a congenital abnormality characterised by the partial or complete absence of the radius. The longitudinal hemimelia indicates the absence of one or more bones along the preaxial (medial) or postaxial (lateral) side of the limb. Preaxial limb defects occurred more frequently with a combination of microtia, esophageal atresia, anorectal atresia, heart defects, unilateral kidney dysgenesis, and some axial skeletal defects. Postaxial acrofacial dysostoses are characterised by distinctive facies and postaxial limb deficiencies, involving the 5(th )finger, metacarpal/ulnar/fibular/and metatarsal. CASE PRESENTATION: The patient, an 8-year-old-boy with minimal craniofacial dysmorphic features but with profound upper limb defects of bilateral and symmetrical absence of the radius and the thumbs respectively. In addition, there was a unilateral tibio-fibular hypoplasia (hemimelia) associated with hypoplasia of the terminal phalanges and malsegmentation of the upper thoracic vertebrae, causing effectively the development of thoracic kyphosis. CONCLUSION: In the typical form of the preaxial acrofacial dysostosis, there are aberrations in the development of the first and second branchial arches and limb buds. The craniofacial dysmorphic features are characteristic such as micrognathia, zygomatic hypoplasia, cleft palate, and preaxial limb defects. Nager and de Reynier in 1948, who used the term acrofacial dysostosis (AFD) to distinguish the condition from mandibulofacial dysostosis. Neither the facial features nor the limb defects in our present patient appear to be absolutely typical with the previously reported cases of AFD. Our patient expands the phenotype of syndromic preaxial limb malformation complex. He might represent a new syndromic entity of mild naso-maxillary malformation in connection with axial and extra-axial malformation complex.